Documenting the languages of the Orang Asli of Malaysia: Some ethical concerns - Nambiar, Mohana Kumbari; Govindasamy, Subramaniam (Elsevier, 2010)
Attempts to document the languages of indigenous communities which are facing the threat of extinction in linguistically diverse countries like Malaysia have given rise to numerous ethical issues, partly due to the disadvantaged and illiterate statuses of these minority communities. This paper explores some of these concerns such as that of obtaining informed consent, privacy and intrusion, withholding of information, data abuse, monetary rewards and cultural sensitivities in documenting the languages of six Orang Asli or indigenous groups in Malaysia. The study is based on the narratives of researchers in the field who were asked to introspect on their experiences in documenting the languages of the Orang Asli.